(untitled) (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-1-68-77 An enormous flow of foreign lexical units into the Russian language is caused by a number of extra-linguistic and intra-linguistic reasons. The whole experience of foreign advertising is borrowed and in particular the technique of creation of advertising messages, which has led to the use of English borrowings in Russian. The purpose of the article is to describe and classify thematic groups of English borrowings of the semantic field “beauty”, based on the material of Russian glossy female magazines. Classification thematic groups of English borrowings of the semantic field “beauty” in Russian glossy female magazines are widely spread and relevant, which devoted to beauty, care, makeup types and vocabulary related to the beauty industry. English borrowings presented in these groups are the most common and well-known, since the beauty industry occupies a significant place in the world. Editors of glossy magazines, authors of articles and advertising messages resort to using a huge number of Anglicisms in order to interest the reader with novelty, expression, thereby increasing the sales of magazines and accordingly advertised goods, the demand for appropriate services in the beauty industry. Such a universal interest in beauty in all its manifestations predetermined the folding of the metalanguage as a system of signs and certain discursive resources. A relevant feature of the modern Russian language and metalanguage of the beauty industry is the use of English borrowings, which are typical of this sphere, in all studied glossy publications. Based on the list of given examples and classification, we can confidently say that English borrowings are firmly entered in the living space of the advertising text. The reasons for the extralinguistic and intra-linguistic nature played a significant role in expanding the lexical-semantic system of the Russian language. Keywords: English borrowings, classification thematic groups, semantic field, beauty, glossy, female magazines.